MO450: A New Hematuria Score, Semi-Quantitative Analysis of Hematuria Normalized for Urine Concentration Predicts the Progression of Chronic Kidney Disease: From the KNOW-CKD Study. (3rd May 2022) - Koh, Jaehee; Min Jo, Sang; Kim, Sangeun; Hoon Jung, Sung; Lee, Kyu-Beck; Kim, Hyang; Oh, Kook-Hwan; Youl Hyun, Young
Abstract: BACKGROUND AND AIMS: It is unclear whether hematuria is a risk factor for chronic kidney disease (CKD) progression. In addition, quantitative evaluation considering urine concentration as in proteinuria has not been established in hematuria. The aim of this study is to verify the relationship between semi-quantitative analysis of hematuria normalized for urine concentration and the progression in CKD. METHOD: We analyzed 1909 patients with pre-dialysis CKD from KNOW-CKD cohort who assessed baseline urine microscopy. Patients were scored according to the number of red blood cells (RBC) in high power field (1 point for < 1, 2 points for 1–4, 3 points for 5̵119 and 4 points for ≥ 20). To obtain the hematuria score, these points were divided by the random urine creatinine level and multiplied by 100. The study endpoint was CKD progression, defined as a composite of a ≥ 50% decrease in estimated glomerular filtration rate (eGFR) from baseline values or end-stage kidney disease. RESULTS: The hematuria score ranged from 1.86 to 20.3 (2.2 ± 1.86). During a median follow-up of 4.6 years (9657 person-years), 729 patients reached study endpoint. There was a graded association between hematuria score and the risk of progression of CKD. The hazard ratios (95% confidence intervals) for second, third and fourth quartile of hematuria score were 1.32 (1.04–1.67), 1.43 (1.12–1.82) and 1.50 (1.17–1.91), respectively, compared to the first quartile. For each 1 point increase in hematuria score, the risk of progression increased by 5%. CONCLUSION: This study showed that there was a graded relationship between a new hematuria score and the risk of the progression of CKD. Microscopic hematuria is a risk factor for CKD progression and might be used as a quantitative risk assessment tool.